The importance of Physical Education in integrated secondary education: teaching conception in the IFCE Campus Canindé (Research, Society and Development, 2019)
The present article aims to analyze the teaching conceptions regarding the importance that they attribute to the discipline of Physical Education for the integrated high school students of the IFCE, Campus Canindé. The research consists of a cut of the master's thesis developed in the Post-graduation Program in Professional and Technological Education (PROFEPT). It is characterized as qualitative and exploratory research. Semistructured interviews were carried out with three teachers who work in the secondary school integrated in this institution. The results show that the teachers consider Physical Education important in the overall development of the student, through the perception and corporal consciousness, as well as the relation that establishes itself in society, when positioning before the mediatic influences presented on the corporal standard not always compatible with healthy life. It was also pointed out that the contributions of the discipline serve the students in promoting an active and healthy lifestyle, and there is also the possibility of future professional action related to the area of Physical Education. Faced with this, it is considered important to strengthen the pedagogical view of the teacher in order to reflect working conditions and the ways in which the body, corporal practices and sport are used as instruments for the effectiveness of power relations and exploitation , it should be noted that integrated secondary education has as its premise the critical formation of the subject before social structures.